Restriction polymorphism maps of Neurospora crassa: updates - R. L. Metzenberg; J. Grotelueschen (Fungal Genetics Reports, 1988)
When a gene or an unidentified fragment of DNA from an organism has been cloned, it is often useful to map its site of chromosomal origin with respect to known markers.